Prinsip Good Governance Dalam Penyalahgunaan Wewenang - Jemmy Jefry Pietersz (SASI, 2017)
governance is a way implemented by the government using political, economic and administrative authority in managing economic and social resources for community development. The term governance is more directed to technical matters of governance in a country. By that, the term governance in relation to good governance is directed more towards legal aspects, especially administrative law which in essence more emphasized public service aspect which is addressed to society. Good governance characteristics include Participation, Rule of law, Transparency, Responsiveness, Consensus orientation, Equity, Effectiveness and efficiency, Accountability, and Strategic vision. These characteristics are legally sourced on two main grounds, namely the principle of the rule of law and the principle of democracy. The principle of the rule of law becomes the foundation of good governance where every act of government should have a legal basis, in the form of authority, procedure and substance and protection of human rights. The principle of a legal state provides the basis of legality in the administration of government, while the principle of democracy as the basis of government openness and community participation. Power or power essentially contains the rights and obligations of the apparatus of government to take certain legal actions, derived from attribution, delegation and mandate. Abuse of power is an act of government that is inconsistent with the purpose of authorization. the form of abuse of power consists of illegal state administration (onrechtmatige overheidsdaad), the misuse of the state administration (detournement de pouvoir or ultra vires) and the arbitrary acts of state administration (abus de droit). Abuse of power may occur against bound and free power. Parameters testing abuse of power from power are tied to the legality of government action, while the abuse of power from free power using the Good Governance Principles (GGP). GGP is the principle of proper administration